Inverted U-Shaped Association of Soluble Transferrin Receptor Concentrations with Risks of Cardiovascular Diseases in Overweight Individuals: A Cross-Sectional Study - Xiao Hu; Jing Xu; Yang Gu (Reviews in Cardiovascular Medicine, 2024)
Background: Iron metabolism may play a role in cardiovascular disease (CVD) pathogenesis. The association between iron metabolism and CVD has yet to be fully investigated. This study evaluated whether iron metabolism was associated with CVD risk and whether the body mass index (BMI) of US adults varied the association. Methods: A cross-sectional study was performed using the National Health and Nutrition Examination Survey (NHANES), conducted from 2017 to 2018. Generalized additive models (GAMs) and multivariable logistic regression were adopted to analyze the association between iron metabolism (serum iron (SI), serum ferritin (SF), transferrin saturation (TSAT), and soluble transferrin receptor (sTfR)) and CVD risk. Further, stratified analysis was conducted to identify patients with high CVD risk. Results: Participants with CVD tended to have significantly increased levels of sTfR (p < 0.001) and decreased levels of TSAT (p < 0.001) and SI (p < 0.001). After adjusting for confounding factors, sTfR levels had a significant positive association with CVD risk (Q1 as reference, Q4 odds ratio (OR) 2.1, 95% CI 1.54–2.87, p < 0.001). Notably, the association between sTfR and CVD risk differed in the BMI subgroup (p for interaction < 0.05). We identified an inverted U-shaped relationship between sTfR and the CVD risk in the group of overweight individuals (non-linear p < 0.001). When the sTfR level was below the turning point (sTfR = 5.35 mg/L), a per unit increase in the sTfR level was correlated with a 78% greater adjusted OR of CVD risk (OR, 1.78 [1.44, 2.19]). Conclusions: Increased sTfR levels were non-linearly related to the CVD risk in the overweight population.